Hubungan Partisipasi Penyusunan Standar, Keketatan Standar dan Insentif Berbasis Standar dengan Kinerja (Pengujian Hubungan Langsung dan Tidak Langsung) - Murwaningsari, Etty (Faculty of Economics Universitas Atma Jaya Yogyakarta, 2009)
This Ã‚Â research Ã‚Â aims Ã‚Â to Ã‚Â investigate Ã‚Â the Ã‚Â relationship Ã‚Â between Ã‚Â participative standard Ã‚Â setting,Ã‚Â standard Ã‚Â tightness Ã‚Â and Ã‚Â standard-based Ã‚Â incentives Ã‚Â toward public Ã‚Â accountant Ã‚Â performance Ã‚Â andÃ‚Â work-related stress. The research examined 16 Jakarta-based public accounting firms in 2007Ã‚Â involving Ã‚Â 213 Ã‚Â respondentsÃ¢â‚¬â€œÃ¢â‚¬â€œ112 Ã‚Â from Ã‚Â big-four Ã‚Â public Ã‚Â accounting Ã‚Â firms Ã‚Â and Ã‚Â 101 Ã‚Â from Ã‚Â non-big-four public accounting firms. The statistical method used to test the hypothesis is the StructuralÃ‚Â Equation Model (SEM). Empirical results from observing a big-four public accounting firm using aÃ‚Â direct model examining five variables show that four variables have significant correlation, whileÃ‚Â an Ã‚Â indirect Ã‚Â model Ã‚Â examining Ã‚Â six variables Ã‚Â results Ã‚Â in Ã‚Â two Ã‚Â variables Ã‚Â have Ã‚Â significant Ã‚Â correlation.Ã‚Â Moreover, an observation of a non-big-four public accounting firm using a direct model examiningÃ‚Â five Ã‚Â variables Ã‚Â show Ã‚Â that Ã‚Â four Ã‚Â variables Ã‚Â have Ã‚Â significant Ã‚Â correlation, while Ã‚Â examination Ã‚Â of Ã‚Â sixÃ‚Â variables using an indirect model found that five variables have significant correlation.